ANALISIS PENGAMBILAN KEPUTUSAN PENENTUAN LOKASI SENTRA OLEH-OLEH KHAS BATAM - Nofriani Fajrah; Sri Zetli (Universitas Putera Batam, 2020)
Batam is developing into a tourism city, however, Batam tourism has not been supported by the souvenir center to sell local people's work. There are several tourist center areas in Batam, but they have not specifically sold special souvenirs from Batam. This study aims to determine the right location for a typical souvenir center of Batam based on a decision analysis of the factors of tourist interest. The method used in this study is the Analytical Hierarchy Process (AHP) by using six variables of tourist interests, which were obtained from previous studies, namely the existence of a tourist center, accessibility, accommodation, transportation, culinary services and the availability of souvenir products. The six variables are paired with the five tourist center areas in Batam, which are obtained based on the results of the researcher's field survey. The decision analysis was carried out by three respondents who are relevant to this study, namely the government, small and medium enterprises, and academics who have expertise in the relevant fields. Based on the research results, it was found that the right location for a typical souvenir center of Batam, Nagoya. This is because Nagoya is the iconic center of Batam with the biggest shopping mall, so tourists will definitely visit Nagoya as an experience of traveling to Batam to buy various kinds of souvenir products from food, drinks, clothes, bags, shoes, perfume and various other accessories. Based on this research, it can be concluded that the existence of an important souvenir center is considered by stakeholders in developing tourism in Batam, so that the local culture of Batam is better known by tourists by buying typical Batam souvenirs at souvenir centers and can also improve the economy of the local population by producing Batam souvenirs